PhD. Kathleen Costales La paradoja en Gracián: “monstruo de la verdad” - Costales, Kathleen (2018)
PARADOX IN GRACIÁN: "MONSTER OF TRUTH" Few works study the use of paradox in Gracián. This is surprising, given that the Baroque had a tendency toward antithesis and contraposition, and paradox, therefore, becomes the most logical linguistic articulation of this way of seeking the inherent oppositions in the world. This scarcity of studies should also surprise us, as this tendency manifests itself frequently in the works of Gracián himself. I propose to study how Gracián develops the concept of paradox in his style manual Agudeza y arte del ingenio, and study the way he puts into practice his own theories regarding the circumstances in which this concept can be used. I analyze his ideas about paradox and apply these to Oráculo Manual, tracing his use of this technique in the second text and studying some examples of paradox to determine if the author follows his own advice regarding the appropriate use of paradox.